2012
DOI: 10.2174/138527212798993112
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Complexes of Molybdenum and their Catalytic Activity

Abstract: This is a review of the published papers that focus on the reactivity of carbonyl complexes of molybdenum in low oxidation states (usually zero or two) and possible applications of molybdenum complexes as precursors of catalysts in different reactions of unsaturated organic substrates such as alkenes and alkynes. The following reactions are analyzed: metathesis, metathesis polymerization, free radical reactions of alkenes, hydrogenation, hydrosilylation, hydrogermylation, hydrostannation, hydroarylation, asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…However, less attention has been paid to early transition metal-mediated ATRA reactions due to the difficulty to control the redox behavior. [26,27] Interestingly, transition metal dinuclear complexes of main group 5 (Nb and Ta), 6 (Cr, Mo and W) and 7 (Re) are more inclined to form multiple bonds between two metal centers. These compounds have been shown to display some inherent characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, less attention has been paid to early transition metal-mediated ATRA reactions due to the difficulty to control the redox behavior. [26,27] Interestingly, transition metal dinuclear complexes of main group 5 (Nb and Ta), 6 (Cr, Mo and W) and 7 (Re) are more inclined to form multiple bonds between two metal centers. These compounds have been shown to display some inherent characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a large number of research groups reported about the ATRA using late transition metals such as Ru, Cu, and Fe . However, early transition-metal-catalyzed ATRA reactions were less explored due to the difficulty to control the reversible redox processes . Recently, we demonstrated that the quadruply bonded dimolybdenum complexes of the Mo 2 L 4 and [ n Bu 4 N] 2 [Mo 2 L 2 Cl 4 ] (L = carboxylate, formamidinate and guanidinate) types are effective catalysts for radical addition and polymerization as well as hydrodehalogenation reactions .…”
Section: Introductionmentioning
confidence: 99%
“…In order to devise similar systems, but neutral ones, we study the structure and electronic properties of similar nanoballs with either Cr or Mo, rather than Pd +2 . It is well known that these two transition metals can form neutral coordination compounds [ 29 , 30 , 31 , 32 ] and planar structures [ 33 , 34 , 35 ] that allow these nanoballs to exist.…”
Section: Introductionmentioning
confidence: 99%